The effect of using multimedia in both individual and group methods for some motor skills on the parallel bars - Kazem, Asst.L.Fatima Ahmed; Al-Shamkhi, Asst.L.Ali Hussein (Sulaimani Journal for Humanities, 2026)
This study aims to reveal the effect of multimedia, both individually and collectively, on learning specific motor skills on parallel lines in men's gymnastics. It also investigates the differences in post-test performance between the two study groups in learning these motor skills. The researcher used the experimental method, as it is suitable for the nature of the study and its problem. The study population consisted of students in the 2023-2024 academic year, while the study sample comprised 20 students, 12 from each department, divided into two experimental groups. The first experimental group used the individual method, while the second group used the group method. The researcher ensured the equivalence of the two groups. Data were collected using personal interviews, questionnaires, tests, and scales. The researcher used the arithmetic mean, standard deviation, percentage, and t-tests for both limited and unlimited samples. The researcher concluded that multimedia, both individually and collectively, facilitated the learning of specific motor skills on parallel lines. The experimental group that used group multimedia showed better performance in learning some motor skills in parallel conditions compared to individual multimedia, and the researcher suggested the need to use multimedia in a group manner due to its positive effect on learning some motor skills in parallel conditions.
Keywords: Multimedia; individual and collective style; parallel device